Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Genome-wide association studies identified novel loci for non-high-density lipoprotein cholesterol and its postprandial lipemic response - Ping An; Robert J. Straka; Toni I. Pollin; Mary F. Feitosa; Mary K. Wojczynski; E. Warwick Daw; Jeffrey R. O’Connell; Quince Gibson; Kathleen A. Ryan; Paul N. Hopkins; Michael Y. Tsai; Chao-Qiang Lai; et al. (Human Genetics, 2014)

Parental transmission of HLA-DRB1*15 in multiple sclerosis - Sreeram V. Ramagopalan; Blanca M. Herrera; Jordana T. Bell; David A. Dyment; Gabriele C. DeLuca; Matthew R. Lincoln; Sarah M. Orton; Michael J. Chao; A. Dessa Sadovnick; George C. Ebers (Human Genetics, 2008)